Continuous or Interval Training and Inflammatory Response in Obese Women - Tenório, Mário César Carvalho (2015)
Background: Recent studies have shown probable benefits of high intensity, predominantly anaerobic activities in fat oxidation capacity. However, the effect of predominantly anaerobic exercise in reducing obesity and inflammatory condition is still little known. Objectives: To assess the effects of aerobic vs. anaerobic training on the levels of C-reactive protein (CRP) in women with central obesity, and the association of CRP levels with body composition. Methods: Randomized clinical trial with a population composed of adult, sedentary women with central obesity, enrolled at the Teaching-Care Outpatient Facility of Escola Bahiana de Medicina e Saúde Pública. A group of 19 women was randomly divided into two groups: Continuous training (CT - intensity at 20% of the ventilatory threshold - VT) or Interval Training (IT - 2-minute stimulus at 120% of VT and 2-minute recovery at 80% of VT) for 10 weeks, twice a week, 20-40-minute sessions. A medical and physical, laboratory and cardiopulmonary assessment was carried out before and after the intervention. Results: Median CRP levels were, respectively, before and after training: CT: 2.2 mg/L (0.6-4.1 mg/L) vs. 2.1 mg/L (0.8-5.5 mg/L) p=0.75; IT: 3.9 mg/L (0.7-8.6 mg/L) vs. 3.2 mg/L (1.2-5.7 mg/L) p=0.90. There was no significant difference when comparing the delta (Δ) CRP levels between groups, p=0.49. There was no association between CRP levels and other pre-intervention variables. Conclusion: Low-volume exercise programs, regardless of their intensity, do not change CRP levels in women with central obesity.